Are we SAFE now? An evaluation of the Seatbelts Are for Everyone teen traffic safety program in Kansas. (17th November 2019) - Freund, Nicole M.; Turosak, Anna; Dean, Amber; White, Hannah
Abstract: Objective: Teens represent the highest risk group for automobile accidents and are almost 3 times as likely to be killed in an accident. Seat belt use interventions are one way to address this issue, and a student-led program in Kansas called Seatbelts Are For Everyone (SAFE) has increased seat belt use for the past decade. An evaluation of SAFE enabled decisions to be made about program improvement and expansion. Methods: Mixed methods examined multiple aspects of the SAFE program, including summative and formative results. Researchers investigated the program through (1) a quasi-experimental observation to explore whether seat belt use at schools implementing SAFE for the first time was higher than at non-SAFE and (2) stakeholder interviews at SAFE schools. Each method examined whether SAFE programs accomplished goals set by program staff and how SAFE could better meet schools' needs. Results: Summative results suggest that SAFE affects seat belt use. It is less influential on distracted driving but has a small but significant influence on that behavior. Stakeholders cited infrastructure and functional challenges affecting implementation, highlighting ways in which SAFE program staff could improve program compliance and outcomes. Formative recommendations included curriculum support, sharing among SAFE schools, and increasing student leadership opportunities. Conclusions: The evaluation of SAFE suggests that students are receptive to programs about seat belt and traffic safety. States may consider the recommendations for improvement of this program with other published evaluations and programs to determine how best to implement similar programs in their communities.